PENGARUH FAKTOR SOSIAL EKONOMI TERHADAP PENDAPATAN KOMODITI PALA DI DESA MAMPING KECAMATAN BALANTAK KABUPATEN BANGGAI - Trianto Enteding; Anita Purnama Marowa; Yuni Rustiawati (Fakultas Pertanian Universitas Tompotika Luwuk, 2023)
Plantation crop commodities are quite strategic trade crops in Banggai Regency, so this study aims to determine the influence and relationship of socioeconomic factors on the income of nutmeg farmers in Mamping Village, Balantak District, Banggai Regency. This research has been carried out in Mamping Village, Balantak District, Banggai Regency, from June to August 2022, using quantitative analysis methods, namely income and regression approaches. The results showed the use of land area (X1=0.838) and age (X2=0.047) factors that had a positive influence on income (Y) while the rest (X3= -0.088, X4= -0.049, X5= -0.089) is negative. that is, those that are between the values of regression coefficients 1 and 0. This explains that every addition of X1 and X2 variables by 1% will increase the income of nutmeg farmers by 0.838 and 0.047 respectivelyProduction and Production Factors studied there are 4 variables that affect nutmeg production, namely education (X1), age (X2), family dependents (X3), farming experience (X4). Based on the results of the study, the relationship between socioeconomic factors (land area, age, education level, farming experience, family dependents) on the income of nutmeg farmers in Mamping Village, Balantak District, Banggai Regency correlated obtained the results of nutmeg farming research in Mamping Village of 0.87 showed that variable X has a very strong relationship with nutmeg farming income.